Manufacture of zink anodes by chill casting - E. F. Baranovsky; V. M. Iljushenko; G. P. Korotkin (Литьë и металлургия, 2000)
In the article the authors present results of the investigations of casting zink in cast-iron chills and their use as anodes in electroplates instead of rolled metal.